Developing Early Childhood Curiosity: Experiental Learning within the Framework of Constructivist Philosophy - Nofita Kurniasari; Fihris (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
This research aims to analyze the development of early childhood curiosity through experiential learning within the framework of constructivism philosophy. A qualitative approach with a literature review design is used to explore in-depth data from various sources, such as scientific journals, reference books, and reliable articles relevant to the concept of constructivism, early childhood development, and learning strategies. Data analysis techniques followed the Miles and Huberman model, including data reduction, data presentation and conclusion drawing. The results show that the implementation of constructivism philosophy can be done through project-based learning methods, playing while learning, guided discussions, and the use of props. Direct experience has an important role in stimulating children's curiosity, improving cognitive abilities, and developing social skills. A learning environment that supports exploration, freedom to experiment and collaboration between students is a key factor in the success of this approach. Learning media such as pictures, videos and props are also effective in enriching children's learning experience. Reflection on the learning experience helps children connect new knowledge with existing ones, creating a strong representation in memory. This research makes a social contribution by emphasizing the importance of positive interactions between children, parents and teachers in creating an inclusive and collaborative learning environment. Such collaboration not only stimulates children's curiosity but also hones their communication, empathy and cooperation skills, which ultimately support their development as active and adaptive individuals in society.